Mother, Mothers: Forms and Contents of Maternity. A Simmelian Interpretation of Surrogate Motherhood - Guizzardi, Luca (Simmel Studies, 2021)
Right from its very origins the debate on surrogate motherhood has fed on its own complexity, rather than achieving sure, unambiguous propositions over its goodness or inhumanity. This article offers a Simmelian interpretation of this modern form of maternity. Through Simmelian epistemology, the author identifies the key for overcoming some dilem-mas which have always accompanied the debate over the goodness or otherwise of surrogacy: whether it is the alienation or the realisation of the woman, the role of money and the value of surrogacy as an act of giving life.